EKSPLORASI FOTOGRAFI JALANAN DI KOTA BANDUNG DENGAN TEMA FOTO HITAM PUTIH - Febrika Cahyadi Sammbodo; Jaeni B. Wastap; Sukmawati Saleh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study aims to create street photography works in black and white themes. Street photography is a genre that captures moments of everyday life in public spaces. In this study, black and white themes are used to emphasize composition, contrast, and the power of visual expression in photographic works. The method used in this study is visual observation and qualitative analysis of a series of black and white street photographs taken by the photographer in taking the object photo. These works are analyzed based on the composition, the play of light and shadow, as well as the emotional expression displayed. The results show that black and white themes can create a strong dramatic effect in street photography. High contrast and emphasis on shapes and patterns provide compelling visual acuity. In conclusion, street photography in black and white provides an opportunity to explore strong and intense visual expression. These works have the potential to present an immersive visual experience and invite viewers to contemplate the meanings of everyday life that are hidden behind monochrome colors.